Impacto ambiental de la ivermectina eliminada por bovinos tratados en otoño, sobre la coprofauna y la degradación de la materia fecal en pasturas (tandil, argentina) - L. E. Iglesias; C. A. Saumell; L. A. Fusé; A. L. Lifschitz; E. M. Rodriguez; P. E. Steffan; C. A. Fiel (RIA: Revista Investigaciones Agropecuarias)
A trial was carried out to evaluate the effect of the ivermectin eliminated in the feces of treated calves on the coprofaune and on the physical degradation of dung pats naturally deposited during the autumn in the Tandil zone. Two experimental groups, located in different paddocks, were used. One group was treated subcutaneously with ivermectin (0,2 mg.kg) and the other remained as control group. The spot where feces were naturally evacuated in day 1,3,7,14, and 21 post treatment (dpt) was clearly identify. Fecal pats of each group were sampled at 1,3,7,14,21,30 and 60 days post deposition (dpd). The ivermectin concentration and organic matter percentage were determined and the arthropods present were collected. All the fecal samples of the treated calves presented drug, being samples on 1 and 3 dpt samples those with the higher concentration and higher organic matter content (p<0.05) for the whole experimental period too. Abundance and diversity of arthropods was reduced in samples from treated group (p<0.05). This effect was marked when comparing adults and larvae of nematocera and braquicera diptera and gamasida, actinedida and acaridida acari. Other groups of organisms showed reduced parameters without statistical significance. Also, the highest reductions in abundance and diversity were obtained in fecal samples of treated group at 1, 3 and 7 dpt in agreement with the highest concentration of ivermectin and the highest organic matter percentage. Consistently, the ivermectin eliminated by cattle treated in autumn affect the faecal natural colonization of dung and delays the faecal degradation in the environment